The Coldest Girl In Coldtown - Black, Holly (London Indigo, 2014)
Tina lives in a world where walled cities called Coldtowns exist. In them, quarantined monsters and humans mingle in a decadently bloody mix of predator and prey. It's an eternal party, shown on TV twenty-four hours a day - gorgeous, glamorous, deadly.
Keywords: Vampires -- Romance fiction -- Young adult fiction